The ratification of judges in Peru: Is it compatible with judicial independence? - Figueroa Gutarra, Edwin (2020)
The judges ratification regime, every seven years since the beginning of the judicial career in Peru, has become a complex reality. Added to this is the configuration of a new modality of partial evaluation of judges, every three and a half years. We seek to unravel that these figures are incompatible with the principle of judicial independence, the same as that in Comparative Law is expressed in a statute of indefinite appointment to the position of judge.